Estudo sobre as estratégias utilizadas pelos alunos na resolução de problemas contextualizados em Cabinda/Angola - Jose Lelo Barros Duli (2014)
The research aimed to identify the strategies adopted by students to solve contextualized problems in an investigative perspective in the Mathematics classroom. This research comes as a result of experiences as a student and professor at the School of the Second Cycle of Secondary Education and ISCED Cabinda at Cabinda. In the secondary school, we perceived mathematics teaching methodologies with characteristics of a traditional pedagogical practice, which contradicts the recommendations expressed by the official documents of the Ministry of Education. Based on Ponte, Dante, Skovsmose, among others, we produced a sequence of activities with contextualized problems in an investigative perspective. These activities were applied in classroom, at the Second Cycle of Secondary Education School at Cabinda, with students ranging in age from eighteen to twenty five years, who were not accustomed to solving contextualized problems. We chose to work with a qualitative and ethnographic methodology seeking to understand how these students related to the proposed problems and to identify strategies utilized to solve them in regular classroom setting. The analysis of the observations was based on the historical and cultural perspective of Vygotsky. There was a significant interaction among the student and shared knowledge construction during the resolutions of the problems. The students used varied strategies that allowed them to solve the problems. Among these strategies, we identified some that were more frequent: repetition of words or phrases; rely on more experienced colleagues; use of everyday knowledge to solve the problems. It was observed that students used different strategies according to what they consider necessary to solve the problems. The strategies revealed students working in the zone of proximal development, where knowledge was constructed in a shared way.